Electro‐Optic Function of Liquid Crystal Displays Doped with Poly(γ‐cyclodextrin)‐Protected ZrO2/Au Nanoparticles. Issue 1 (9th June 2016) - Shiraishi, Yukihide; Watanabe, Chiyomi; Sawai, Hiroya; Asano, Hitoshi; Toshima, Naoki
Summary: We prepared poly (γ‐cyclodextrin)‐protected zirconia/gold (PγCyD‐ZrO2 /Au) nanoparticles. Particles in colloidal dispersions of PγCyD‐ZrO2 /Au nanoparticles have an average diameter of 3.1–4.6 nm. The nanoparticles were dispersed in practical liquid crystal (NTN01) to construct novel twisted nematic liquid crystal displays. The response time of this twisted nematic liquid crystal displays in the presence of PγCyD‐ZrO2 /Au nanoparticles was faster than that in the absence of nanoparticles.